2011
DOI: 10.4028/www.scientific.net/msf.678.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Mould Vibration on Solidification Behaviour and Microstructure of A360-SiC<sub>p</sub> Metal-Matrix Composites

Abstract: In this work the microstructural evolution of an A360 alloy reinforced with 10vol.% SiC particulate is described. During the material solidification, mechanical vibration, in the range of 0-41 times the gravity acceleration, g, has been applied to a steel die. It has been observed that vibrations can promote a quite homogeneous SiC dispersion on macroscopic scale. On the other hand, by using too high vibrations’ intensity, segregation phenomena have been pointed out in the castings. Furthermore, it has been ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This is due to the forced convection effect induced by die vibration, which increased the heat transfer coefficient. It is reported that the heat transfer coefficient of casting A360-SiCp composites in stationary die was in the range of 1000-2700 W/m 2 K and that with intensity of die vibration of 29 g was in the range of 1000-10,000 W/m 2 K. 29 It is well known that higher heat transfer coefficient during solidification increases undercooling, which consequently refines microstructure and reduces microsegregation of solutes in a-Al phase.…”
Section: Influence Of Die Vibration On Sdasmentioning
confidence: 97%
“…This is due to the forced convection effect induced by die vibration, which increased the heat transfer coefficient. It is reported that the heat transfer coefficient of casting A360-SiCp composites in stationary die was in the range of 1000-2700 W/m 2 K and that with intensity of die vibration of 29 g was in the range of 1000-10,000 W/m 2 K. 29 It is well known that higher heat transfer coefficient during solidification increases undercooling, which consequently refines microstructure and reduces microsegregation of solutes in a-Al phase.…”
Section: Influence Of Die Vibration On Sdasmentioning
confidence: 97%
“…As an effective research method, numerical simulation is widely used in various fields. Some scholars have used commercial software to simulate the temperature field and flow field of ingots under the vibration condition, which effectively supplements the theory of improving the quality of ingots with vibration technology [7][8][9][10]. However, simulation studies on the impact vibration applied to the solidification end of the continuously-cast billet are rare.…”
Section: Introductionmentioning
confidence: 99%